Origin of the circumflex branch of the coronary artery. A case report - Alves, Nilton [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2008)
The left coronary artery usually supplies the circumflex branch which provides several atrial and ventricular branches. During a routine dissection of the coronary artery, we could detect a circumflex branch originating from the right coronary artery. This resulted in an analysis of another 59 hearts without any similar results.
Keywords: Circumflex branch; Coronary artery